2013
DOI: 10.1016/j.bbamem.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extracellular conductivity on electroporation-mediated molecular delivery

Abstract: In this work, the effect of extra-cellular conductivity on electroporation-mediated molecular delivery efficiency is investigated. A numerical model combining the Smoluchowski equation for membrane permeabilization and the Nernst-Planck equations for ion transport is used to simulate the evolution of ion concentration spatially and temporally. The results are compared with and used to interpret trends observed from previous experimental measurements. Agreements are found which suggest the critical importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 74 publications
2
45
1
Order By: Relevance
“…In one study [51], the authors found that nsEP-created pores "begin to shrink immediately after the pulse ceases, and the majority of them vanish between 180 and 200 ns"; they concluded that the electrophoresis during the pulse plays a dominant role in Pr uptake. However, a different model predicted that "essentially all transmembrane molecular transport occurs post-pulse" [52], which is fully consistent with our experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…In one study [51], the authors found that nsEP-created pores "begin to shrink immediately after the pulse ceases, and the majority of them vanish between 180 and 200 ns"; they concluded that the electrophoresis during the pulse plays a dominant role in Pr uptake. However, a different model predicted that "essentially all transmembrane molecular transport occurs post-pulse" [52], which is fully consistent with our experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the field strength over a critical threshold value expands the permeabilization of the membrane. Although other mechanisms such as endocytosis, diffusion (particularly for small molecules, e.g., MW b 4 kDa), and membrane-DNA interactions may be involved in the delivery process, it has been recognized that the main molecular uptake of charged moderate and large molecules occurs through electrophoresis [18,19,[33][34][35][36][37][38][39][40][41]. The direct current (DC) component of the applied field provides an electrophoretic force for delivering molecules into the cytoplasm [42].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is termed electroporation, and has been used in various research and clinical applications for gene transport and protein or drug delivery [6][7][8][9][10][11][12][13][14]. Besides physiological [15][16][17][18][19][20][21] and cellular [22][23][24][25] variables, the electrical parameters clearly play an important role in the complex electroporation process [26,27]. Transient electropermeabilization of the membrane begins when the applied external field exceeds the critical transmembrane potential [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…This can occur, for instance, under conditions that result in tissue electroporated to a high degree (Z ≈ 1), or by using a treatment protocol where electrokinetic effects (electroosmosis, electrophoresis) are of significant importance, as these are not captured by the model equations(Li & Lin, 2011b;Li, Tan, Yu, & Lin, 2013a;Movahed & Li, 2012;Sadik, Li, Shan, Shreiber, & Lin, 2013). Electrokinetic effects may already be important under conditions used in this study (up to 800 μs pulses).…”
mentioning
confidence: 91%
“…A closer look at the electroporation processes on the biochemical level reveals that treatment outcome and efficacy are largely governed by electrical and (related) chemical properties of the treated material, and mass transport that occurs during and after application of electric pulses (Kotnik et al, 2012;Li & Lin, 2011a;Li, Tan, Yu, & Lin, 2013b;Pucihar, Kotnik, Miklavcic, & Teissie, 2008;Sel et al, 2005). These properties and transport phenomena influence the development of the electropermeabilized state of the cell membrane during electroporation, and continue to be important in the post-pulsation period of pore shrinkage, resealing, cell lysis, etc.…”
Section: Introductionmentioning
confidence: 97%